Current utilization and future directions of robotic-assisted endovascular surgery. (1st September 2020) - Legeza, Peter; Britz, Gavin W.; Loh, Thomas; Lumsden, Alan
ABSTRACT: Introduction: Endovascular surgery has become the standard of care to treat most vascular diseases using a minimally invasive approach. The CorPath system further enhances the potential and enables surgeons to perform robotic-assisted endovascular procedures in interventional cardiology, peripheral vascular surgery, and neurovascular surgery. With the introduction of this technique, the operator can perform multiple steps of endovascular interventions outside of the radiation field with high precision movements even from long-geographical distances. Areas covered: The first and second-generation CorPath systems are currently the only commercially available robotic devices for endovascular surgery. This review article discusses the clinical experiences and outcomes with the robot, the advanced navigational features, and the results with recent hardware and software modifications, which enables the use of the system for neurovascular interventions, and long-distance interventional procedures. Expert opinion: A high procedural success was achieved with the CorPath robotic systems in coronary and peripheral interventions, and the device seems promising in neurovascular procedures. More experience is needed with robotic neurovascular interventions and with complex peripheral arterial cases. In the future, long-distance endovascular surgery can potentially transform the management and treatment of acute myocardial infarction and stroke, with making endovascular care more accessible for patients in remote areas.